Protonema of the moss Funaria hygrometrica can function as a lead (Pb) adsorbent. - Misao Itouga; Manabu Hayatsu; Mayuko Sato; Yuuri Tsuboi; Yukari Kato; Kiminori Toyooka; Suechika Suzuki; Seiji Nakatsuka; Satoshi Kawakami; Jun Kikuchi; Hitoshi Sakakibara (PLoS ONE, 2017)
Water contamination by heavy metals from industrial activities is a serious environmental concern. To mitigate heavy metal toxicity and to recover heavy metals for recycling, biomaterials used in phytoremediation and bio-sorbent filtration have recently drawn renewed attention. The filamentous protonemal cells of the moss Funaria hygrometrica can hyperaccumulate lead (Pb) up to 74% of their dry weight when exposed to solutions containing divalent Pb. Energy-dispersive X-ray spectroscopy revealed that Pb is localized to the cell walls, endoplasmic reticulum-like membrane structures, and chloroplast thylakoids, suggesting that multiple Pb retention mechanisms are operating in living F. hygrometrica. The main Pb-accumulating compartment was the cell wall, and prepared cell-wall fractions could also adsorb Pb. Nuclear magnetic resonance analysis showed that polysaccharides composed of polygalacturonic acid and cellulose probably serve as the most effective Pb-binding components. The adsorption abilities were retained throughout a wide range of pH values, and bound Pb was not desorbed under conditions of high ionic strength. In addition, the moss is highly tolerant to Pb. These results suggest that the moss F. hygrometrica could be a useful tool for the mitigation of Pb-toxicity in wastewater.